Qualitative study on the Community Perception of the Integrated Management of Childhood Illness (IMCI) Implementation in Lahej, Yemen - Basaleem, Huda O (Sultan Qaboos University Medical Journal, College of Medicine & Health Sciences, 2009)
OBJECTIVES: This qualitative study was aimed at exploring the perceptions of community leaders and mothers about health services and community actions pertaining to child health in Lahej, Yemen since the Implementation of Integrated Management of Childhood Illnesses (IMCI) in 2003. METHODS: Face-to-face, semi-structured, in-depth interviews were conducted with six community leaders and seven mothers in 2007 in the three districts of Lahej Governorate, Yemen, that are implementing IMCI. RESULTS: Neither group was aware of IMCI, but had “positive perception to the services.” Community leaders expressed “uncertainty about the role of health committees and community participation,” and said, “people can contribute in different ways” and “health authorities must play a more active role.” The mothers emphasised, “poor livelihood and environmental conditions” and “salient counselling messages not received.” CONCLUSION: The pressing needs for effective community-IMCI is obvious owing to the appalling toll on child health of unfavourable livelihood and environmental conditions and disorganised community initiatives. Thus, for effective IMCI implementation, governmental support needs to be strengthened.